Cyberbullying and problematic Internet use in Colombia, Uruguay and Spain: Cross-cultural study - Yudes-Gómez, Carolina; Baridon-Chauvie, Daniela; González-Cabrera, Joaquín-Manuel (Comunicar, 2018)
The goal of this cross-cultural study was to analyze and compare the cybervictimization and cyberaggression scores, and the problematic Internet use between Spain, Colombia and Uruguay. Despite cultural similarities between the Spanish and the South American contexts, there are few empirical studies that have comparatively examined this issue. The study sample consisted of 2,653 subjects aged 10-18 years. Data was collected through the cyberbullying questionnaire and the Spanish version of the "Revised generalized and problematic Internet use scale". Results showed a higher prevalence of minor cyberbullying behavior in Spain between 10-14 years. In the three countries compared, there was a higher prevalence of two types of bystanders: the defender of the victim and the outsider, although in Colombia there were more profiles of assistant to the bully. Regarding the problematic use of the Internet, there were not differences between the three countries. We provide evidence on the relationship between cybervictimization and cyberaggression and problematic use of the Internet. The dimensions of compulsive use and regulation of mood are the best predictors of cyberbullying. We discuss our results in relation to the possible normalization of violence and its lack of recognition as such.